Based on Social, Economic, and Cultural Aspects, Is The “Tuak” Toraja Business Still Worth Sustaining? - Thana, Dwi Prasetyawati; Padallingan, Yohanis; Amran, Farizah Dhaifina (Jurnal AGRISEP, 2025)
Toraja’s culture is distinct and captivating, with unique traditions passed down through generations. Among them, the tradition of serving and consuming tuak (a traditional alcoholic beverage) stands out, particularly in ceremonies like Rambu Tuka' (thanksgiving) and Rambu Solo' (funeral). Although many view tuak as a drink that can intoxicate and lead to health issues, it also holds potential as a profitable business if seen from a different perspective. This research investigates the business opportunities of Toraja tuak by examining social, economic, and cultural factors to understand how the economic conditions of tuak producers might be improved and gain broader acceptance. The study aims to analyze the viability of tuak as a business, factoring in social, economic, and cultural dimensions. The research is conducted in three stages: first, identifying issues through interviews and FGDs; second, conducting an in-depth literature review and gathering primary data on tuak business opportunities; and third, collecting secondary data, processing and analyzing it, and drawing conclusions. Results indicate that the tuak business holds significant promise when viewed through these comprehensive lenses, offering valuable social, economic, and cultural benefits.